Associations of weight control related behaviors with current cigarette smoking among Chinese adolescents: Results from an ongoing school-based survey in Zhejiang province - Meng Wang; Jue Xu; Haiping Fang; Liping Yang; Tao Yang; Jianqiang Fan; Xiaofu Du; Chunxiao Xu; Yunqi Guan; Jieming Zhong; Min Yu (Tobacco Induced Diseases)
Introduction Previous studies have suggested that adolescents may smoke cigarettes to control weight, but relevant research is scarce in Chinese youth. This study was conducted to examine the associations of weight control related behaviors with cigarette smoking in Chinese students.